COMPARISON OF PHYSIOLOGICAL CHARACTERISTICS OF FINSWIMMING 50 M AND 800 M SURFACE ATHLETES - Suherman, Hadid
Background: Finswimming is a branch of diving which is the result of the development of swimming which distinguishes the use of equipment such as monofin or bifin, and snorkeling. Fisnwimming has been competed on many international levels except for the Olympics. Several studies on the characteristics of finswimming athletes have been conducted. However, research has not found research on the physiological characteristics of finswimming athletes on short and long distance numbers. Data on physiological characteristics of athletes are indispensable for training programs that suit the athlete's own needs. Therefore, this study aims to determine the anthropometric differences between short and long distance finswimming athletes. Thus, it is hoped that this research can provide a more objective understanding in athlete selection and performance programs. Methods: The research method used in this research is quantitative descriptive. The research was carried out in two stages, the first carried out in the National Sports Hospital laboratory and the second carried out in the Bogor City Milakancana swimming pool. The research sample came from Milakancana Bogor finswimming athlete with an age range of 15-17 years. data taken in this study are anthropometric data using stadiometer, body composition data using GE lunar Prodigy DXA, vital capacity data using SP10 Spirometer, VO2max data using Treadmill and Quark CPET Cosmed, and lactic acid data using accutrend plus portanbel lactate in the present study was a quasi-experimental. Result: The average BMI score of 50 M athletes was 24.69 and 800 M athletes 22.07. Significant difference between the difference with the value (p <0.05). Then the average value of fat mass, percentage of total fat, fat mass index, total muscle mass, and muscle mass percentage of 50 M athletes were 24.38 (kg), 32.08 (%), 8.79 (kg / m3), 39.15 (kg), 64.61 (%) and 800M athletes respectively are 10.43 (kg), 16.25 (%), 3.74 (kg / m3), 50, 51 (kg), 79.86 (%). Significant difference between the difference with the value (p <0.001). The average VO2max of 50 M athletes was 50.46 (mL / (kg.min)) and the 800 M athlete was 56.72 (mL / (kg.min)). Significant difference between the difference with the value (p <0.05). Next is the vital vital value (FVC) of 50 M athletes at 3.50 (L) and 800 M athletes at 4.12 (L). Significant difference between the difference with the value (p <0.01). Conclusion: The results show that there are significant differences in anthropometric data, VO2max, FVC between athletes 50 M and 800 M. With these results it is expected that the trainer is able to design an appropriate training program to improve the physical condition of athletes 50 M, so that there is no very big difference on the physical abilities of athletes 50 M when competing.